2021
DOI: 10.1021/acs.jchemed.1c00849
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Ammonia Borane: A Modular, Multifaceted Approach Introducing Experimental Design through Guided Inquiry

Abstract: A practical focusing on the synthesis, isolation, and hydrolysis of ammonia borane (AB), H3N·BH3, was developed for first-year undergraduate students. By requiring students to propose their own experimental setup to measure the amount of gas produced upon hydrolysis, experimental design skills were introduced and developed during the practical. As a result of the COVID-19 pandemic, remote and face-to-face versions of the practical were created to enable inclusivity in which experimental design skills were a ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Undergraduate chemistry majors might typically have opportunities to engage in experimental design in a capstone research experience, but there are many courses throughout the typical undergraduate chemistry program in which such opportunities might be embedded. Various reports describing initiatives to introduce experimental design into courses in the undergraduate chemistry curriculum have appeared in the literature, including recent examples involving general chemistry (Farley et al, 2021;Smallwood et al, 2021;Thomson and Lamie, 2022), analytical chemistry (Doughan and Shahmuradyan, 2022), and biochemistry (Goodey and Talgar, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Undergraduate chemistry majors might typically have opportunities to engage in experimental design in a capstone research experience, but there are many courses throughout the typical undergraduate chemistry program in which such opportunities might be embedded. Various reports describing initiatives to introduce experimental design into courses in the undergraduate chemistry curriculum have appeared in the literature, including recent examples involving general chemistry (Farley et al, 2021;Smallwood et al, 2021;Thomson and Lamie, 2022), analytical chemistry (Doughan and Shahmuradyan, 2022), and biochemistry (Goodey and Talgar, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…We are actively trying to incorporate opportunities for experimental design into the first-year teaching laboratory. Considering that experimental design and inquiry-based practicals require significant scaffolding and support, this article demonstrates a further application of such a pedagogical approach: the introduction of fully scaffolded expository practical protocols, followed by the posing of a “research” question which students have to consider and investigate.…”
Section: Introductionmentioning
confidence: 99%
“…Encouragingly, incorporating experimental design components into the curriculum has been featured in new and revised experiments for both general chemistry ,, and upper-division, subdisciplinary laboratories. , One recent article presented a method to introduce design into existing curricula by creating a two-week experience in which a traditional laboratory is followed by a similar experiment in an authentic context where students design the experiment. For acid–base chemistry, although guided discovery buffer experiments have been published, , less has been done specifically to develop inquiry laboratory activities that facilitate student understanding of titrations, especially within real-world applications.…”
Section: Introductionmentioning
confidence: 99%
“…16 Additionally, a review of 13 published "inquiry" chemistry laboratory manuals found that only 11% of experiments qualified as guided or open inquiry according to the authors' developed rubric. 17,18 Encouragingly, incorporating experimental design components into the curriculum has been featured in new and revised experiments for both general chemistry 12,19,20 and upperdivision, subdisciplinary laboratories. 15,21 One recent article presented a method to introduce design into existing curricula 19 by creating a two-week experience in which a traditional laboratory is followed by a similar experiment in an authentic context where students design the experiment.…”
Section: ■ Introductionmentioning
confidence: 99%